The Protective Effects of Danggui-Baizhu-Tang on High-Fat Diet-Induced Obesity in Mice by Activating Thermogenesis - Zhao, Lijun; Zhu, Xiaoqiang; Cong, Renhuai; Yang, Xiangliang; Zhu, Yanhong (Frontiers in Pharmacology, 2018)
Danggui-Baizhu-Tang (DBT), a traditional Chinese medicine decoction, was used for decreasing serum TG and TC remarkably. However, effect of weight control and action mechanism remains confused. In this study, to evaluate the anti-obesity effects, different gradient concentration of DBT (0.59 g/kg, 1.17 g/kg) or Orlistat (Orl, 15.6 mg/kg; positive control) were administrated by gavage for eight weeks in C57BL/6J mice which were pretreated with chow of high fat diet (HFD) for three months. After administration, significant decrease of body weight and food utilization was observed. It was indicated that concentration of triacylglycerol (TG), total cholesterol (TC), alanine aminotransferase (ALT), aspartate aminotransferase (AST) in serum were reduced strikingly, as well as accumulation of lipid droplets in liver. Meanwhile, DBT treatment could also decrease weight of white adipose tissue (WAT) and size of adipocytes, whereas increase weight of brown adipose tissue (BAT) in mice. Moreover, it was revealed that DBT could elevate rectal temperature by raising expression of uncoupling protein-1 (UCP1) and peroxisome proliferator-activated receptor-gamma coactivator-1alpha (PGC-1α), which were attributed to phosphorylation of AMP-activated protein kinase (AMPK). Furthermore, TNF-α and IL-6, obesity-related inflammatory cytokines, were decreased. In conclusion, DBT could stimulate phosphorylation of AMPK to raise expression of UCP1 and PGC-1α, and activate thermogenesis to prevent obesity.